2006
DOI: 10.1002/pen.20488
|View full text |Cite
|
Sign up to set email alerts
|

Temperature evolution during stereolithography building with a commercial epoxy resin

Abstract: In this study, the temperature evolution during stereolithography (SL) processing of a commercial epoxy resin is experimentally measured and numerically simulated. Experimental tests were performed in a SL equipment to evaluate the temperature increase during laser‐activated photopolymerization. Temperatures on the resin surface were measured with a thermal video system in both static and moving laser experiments. For the moving laser experiments, the effect of the energy dose was tested by using different vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Alumina drill bits (left) light energy released for one single exposure and the evoked heat of reaction in a mathematical model. Corcione et al [228] proved that the temperature rise within the photosensitized liquid is proportional to the applied energy dose during an exposure, the distance from the center of the light beam, as well as the inverse of the scanning speed.…”
Section: General Principlementioning
confidence: 99%
“…Alumina drill bits (left) light energy released for one single exposure and the evoked heat of reaction in a mathematical model. Corcione et al [228] proved that the temperature rise within the photosensitized liquid is proportional to the applied energy dose during an exposure, the distance from the center of the light beam, as well as the inverse of the scanning speed.…”
Section: General Principlementioning
confidence: 99%
“…Likewise, temperature profile has an important role on quality. Corcione et al (2006) found that temperature increase on vat surface is dependent on energy dose during SL process. Lower scan speed leads to higher temperatures and reaction rates, which involve shrinkage and curl distortion (Corcione et al, 2006).…”
Section: Overview Of Quality Control In Additive Manufacturingmentioning
confidence: 97%
“…Corcione et al (2006) found that temperature increase on vat surface is dependent on energy dose during SL process. Lower scan speed leads to higher temperatures and reaction rates, which involve shrinkage and curl distortion (Corcione et al, 2006). Lee et al (2007) studied the effects of laser energy with respect to thickness of building part and laser speed.…”
Section: Overview Of Quality Control In Additive Manufacturingmentioning
confidence: 97%
“…The spatially inhomogeneous initiation rates result in a gradient in double bond conversion along the beam direction. Photopolymerization kinetics of dimethacrylate copolymers under isothermal conditions has been widely studied [8][9][10][11]; however, the study of the photopolymerization reactions under nonisothermal conditions has not received the same attention despite its significance in real-life applications. The polymerization reaction is highly exothermic, which results in an increase in the sample temperature during the process and this effect becomes more important as the sample thickness increases.…”
Section: Introductionmentioning
confidence: 99%